2008
DOI: 10.1016/j.ejrex.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon co-localization of pituitary adenoma and parasellar cavernous angioma

Abstract: We encountered a 49-year-old female presenting with left oculomotor palsy who was found to be co-localized cavernous sinus CA and pituitary adenoma. Although cavernous angiomas (CA) originated from parasellar regions are not so rare, on neuroimaging studies, the characteristics of CA may be difficult to differentiate from those of pituitary adenomas. The co-localization of the two tumors was identified by preoperative dynamic MRI study. As intraoperative histological examination confirmed our preoperative diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This lesion initially is peripherally and then progressively totally homogeneous contrast enhanced. This contrast pattern is similar to other extra-cranial CH cases such as liver CHs [12]. In the literature, it was reported that while in a cavernous sinus CH, in coronal image, patchy peripheral contrast enhancement was observed, in axial image homogeneous contrast was enhanced [13].…”
Section: Discussionmentioning
confidence: 53%
“…This lesion initially is peripherally and then progressively totally homogeneous contrast enhanced. This contrast pattern is similar to other extra-cranial CH cases such as liver CHs [12]. In the literature, it was reported that while in a cavernous sinus CH, in coronal image, patchy peripheral contrast enhancement was observed, in axial image homogeneous contrast was enhanced [13].…”
Section: Discussionmentioning
confidence: 53%
“…On MRI, SCH is usually with well-defined borders; brightly hyperintense on T2WI images and might show either of two patterns of contrast enhancement – a rapid homogeneous enhancement or a progressive centripetal enhancement. Centripetal enhancement is where contrast fills the peripheral part of the lesion in the early stage of dynamic scanning (routinely performed with sellar MRI to detect pituitary adenomas) and then slowly fills the entire lesion in a pattern similarly seen in extra-cranial cavernous hemangiomas as those in the liver[ 15 , 27 ]. Furthermore, infrequently the T2 signal characteristics of SCH enclose few signal void areas suggesting its vascular nature[ 31 ].…”
Section: Discussionmentioning
confidence: 99%